Risk Analysis of Consumer Goods Industry Shares on the Indonesia Stock Exchange - Rahma Sari Harahap (Institute of Computer Science (IOCS), 2021)
In investation, an investor will face two elements related to the capitals or funds which were invested such as return and risk. Both of these elements have a positive correlation. Basically, the greater the returns obtained, the greater the risks it have, indeed the smaller the returns obtained, the smaller the risks it have. The purposes of this study were to find out and to analyze any differences of systematic risks and unsystematic risks of Food and Beverages subsector, Tobacco Manufacturers subsector, Pharmaceuticals subsector, Cosmetics and Household subsector, and Houseware subsector in Consumer Goods Industry sector that were listed in Indonesia Stock Exchange. The study methods used for this study were data analysis and descriptive analysis. The datas used for this study were secondary data such as 34 Consumer Goods Industry sector companies’ stock price in Indonesia Stock Exchange and Jakarta Composite Index from 2012 January 1st until 2012 December 31st. The hypothesis testing was done by using One Way ANOVA test and Independent Samples t-test with a significance level of 5%. One Way ANOVA test result shows that there were no systematic risk differences among Food and Beverages subsector, Tobacco Manufacturers subsector, Pharmaceuticals subsector, Cosmetics and Household subsector, and Houseware subsector in Consumer Goods Industry sector that were listed in Indonesia Stock Exchange. The other One Way ANOVA test shows that there were differences among Food and Beverages subsector, Tobacco Manufacturers subsector, Pharmaceuticals subsector, Cosmetics and Household subsector, and Houseware subsector in Consumer Goods Industry sector that were listed in Indonesia Stock Exchange. These differences then were seen in Post Hoc test and Independent Samples t-test. It has been seen that Food and Beverages subsector has a greater unsystematic risk from those of Tobacco Manufacturers subsector and Cosmetics and Household subsector, and then Houseware subsector has a greater unsystematic risk from those of Cosmetics and Household Subsector.